Bone-implant interface in orthopedic surgery : basic science to clinical applications - Karachalios, Theofilos (Springer London, 2014)
What is the optimal design and fixation of the implants we use for orthopedic reconstructions? What is the gold standard for the management of patients requiring implants? Is there scope for improvement still further?   Huge efforts have been made both by research scientists in orthopedics and the implant industry to furthering the options available for arthroplasty  without necessarily considering the cost-effectiveness of this research to clinical outcomes. It has also become apparent that theoretical and laboratory studies do not always match the results of long-term clinical studies of which there regretfully few of sufficient quality.   The Editor and his carefully chosen selection of contributors critically evaluate data from basic science, experimental in vivo and in vitro biological and mechanical models, autopsy specimens and long-term clinical studies to answer these questions.   Bone-Implant Interface in Orthopedic Surgery: Basic Science to Clinical Applications focuses on the bone-orthopedic implant interface in general and will be useful both for the novice who seeks a quick introduction to this specific topic and for more experienced surgeons who seek an in depth critical review of current practices.